2015
DOI: 10.1111/febs.13366
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the adipokinetic hormone/corazonin‐related peptide signaling system in Rhodnius prolixus

Abstract: The mammalian gonadotropin‐releasing hormone is evolutionarily related to the arthropod adipokinetic hormone and the recently discovered adipokinetic hormone/corazonin‐related peptide (ACP). The function of the ACP signaling system in arthropods is currently unknown. In the present study, we identify and characterize the ACP signaling system in the kissing bug Rhodnius prolixus. We isolated the complete cDNA sequence encoding R. prolixus ACP (Rhopr‐ACP) and examined its expression pattern. Rhopr‐ACP is predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 35 publications
5
35
0
4
Order By: Relevance
“…ACP has been demonstrated to act as a neurohormone in the central nervous system of Rhodnius prolixus 88, however we only detected expression of Cq -ACP in the eyestalk of C. quadricarinatus . Temporal expression profiling shows that both Rhopr-ACP and Rhopr-ACPR are upregulated after ecdysis, and the author suggested that this neuropeptide may be involved in processes associated with post-ecdysis89. Still, little is known about the function of this neuropeptide.…”
Section: Discussionmentioning
confidence: 99%
“…ACP has been demonstrated to act as a neurohormone in the central nervous system of Rhodnius prolixus 88, however we only detected expression of Cq -ACP in the eyestalk of C. quadricarinatus . Temporal expression profiling shows that both Rhopr-ACP and Rhopr-ACPR are upregulated after ecdysis, and the author suggested that this neuropeptide may be involved in processes associated with post-ecdysis89. Still, little is known about the function of this neuropeptide.…”
Section: Discussionmentioning
confidence: 99%
“…RNAi mediated knockdown of the ACP receptor in T. castaneum has no effect on physical appearance, egg number and mortality. Both ACP and its receptor are predominantly expressed in the CNS of T. castaneum [195], R. prolixus [166] and A. aegypti [211], which indicates a neuromodulatory role for this signaling system. In addition, the temporal expression profile data suggest that ACP could be involved in post-ecdysis related processes [166,211].…”
Section: Neuropeptides Lost In Drosophilamentioning
confidence: 95%
“…ACP has a broader distribution in mosquitoes where ACP-like immunoreactivity was also detected in neurons in thoracic ganglia [221]. ACP may act as a central neuromodulator, since its receptor is predominantly found in the central nervous system [166,195]. The specific function of ACP signaling remains unknown, although its temporal expression suggests that it may play a role in development and/or ecdysis [166,195,211].…”
Section: Adipokinetic Hormone/corazonin-related Peptide (Acp)mentioning
confidence: 99%
“…The structural and sequential analysis described this neuropeptide in several insects, including anophelines. ACP is primarily expressed in the nervous system and, to a lesser extent, in other insect organs and tissues [110,111]. ACP transcripts were detected in the head and thorax of larvae, pupae, and adult of Ae.…”
Section: Discussionmentioning
confidence: 99%